A TEXTBOOK ANALYSIS OF “ COMMON MISTAKES IN ENGLISH “ : A Textbook for The Intermediate Level - Syahid, Abdul; Hairunnisa , Fanny; Liswati, Helli Ramdanniah; Kusumaningrum, Tria Angela; Siliwangi , Diah Puji; Annazah , Syafina (Asosiasi Dosen Muda Indonesia, 2024)
This study looks into common mistakes made by English as a Foreign Language (EFL) learners by using and analyzing a textbook with the title “Common Mistakes in English” by T.J. Fitikides, intending to identify contributing factors, offer effective solutions, and examine practical relevance in real-world EFL contexts. To eliminate ambiguity and promote better and clearer communication, this study exclusively employs interviews to identify factors contributing to English errors, particularly in family life and the educational environment. By delving into the complexities of English language learning, this study hopes to provide practical strategies for improving proficiency, resulting in smoother communication and comprehension in both personal and professional settings. Finally, this study adds to ongoing efforts to improve English language proficiency among EFL learners, thereby promoting better cross-cultural communication and understanding.